Mobile internet and income improvement: Evidence from Viet Nam - Trang Thi Pham (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
New developments of existing technologies over time have led to emergent patterns of technology adoption and, accordingly, changing impacts on economy and society. Focusing on the arrival of mobile internet in the early 2010s in developing countries, this paperidentifiessignificant positive effects on provinces' average household income in Viet Nam. The effect sizes are larger for lower-income quintiles and for rural areas, suggesting the more inclusive changing impact of the innovation over the last decade. Preliminary evidence of impact mechanisms via skilled employment rates and (formal) wages is also presented. The evidence from Viet Nam, a lowermiddle-income country, can bring further understanding in terms of the extent of development impacts of second-generation mobile for development (M4D 2.0) in particular and information and communication technologies for development (ICT4D) in general.
Keywords: D31; O30; O53; R50; 330; household income; mobile internet; smartphone; technological change; developing countries; M4D; ICT4D